Finite Element Comparative Analysis of Von Mises Stress Levels in Unilateral Removable Partial Denture with and without Distal Implant - Andrei, Oana Cella; Tănăsescu, Livia Alice; Tărlungeanu, Ioana Daniela; Dina, Magdalena Natalia; Tierean, Mircea Horia (MDPI AG, 2022)
The aim of this paper is to compare von Mises stress levels and displacements between two possible designs of a class II Kennedy unilateral removable partial denture. Finite element anal-ysis was used to compare two unilateral class II Kennedy removable partial dentures replacing mandibular second premolar, first and second molars and having the same design, excepting a distal implant. The 3D model was created for a mandibular RPD with three artificial teeth and double ball attachment on the abutment teeth and a horizontal ball attachment for the implant, using Autodesk Inventor 2022 software. On the saddle, significant differences appear only when force is applied on the second molar. Association with implant increases von Mises stresses on the acrylic saddle, displacements values being similar, and decreases von Mises stresses on the mu-co-osseous support, displacements values being also similar. Regarding the metal reinforcement of the denture, von Mises stress values are greater for forces applied on the second premolar in the implant situation, and smaller for forces applied on the first and second molars. Association with implant decreases von Mises stresses on the metal reinforcement of the denture only if the force is applied distally, on the two molars; in this case, the metal reinforcement is more stressed above the mesial double ball attachment, displacements values being similar. Regarding the artificial teeth, adding a distal implant does not significantly influence the stress and displacements values, excepting on the second premolar where the von Mises stresses values are greater, dis-placements values being similar. Although association with implant is increasing the risk of fracture for the denture, the results demonstrate that in the posterior area of the edentulous space the denture is exerting less pressure on the mucosa and subjacent bone, protecting the area against resorption.
Keywords: unilateral removable partial denture; dental implant; finite element analysis